Diffusion properties of hydrogen in B2-TiFe - Kulkova, Svetlana E. (Physical Mesomechanics)
The diffusion properties of hydrogen in B2-TiFe alloy were studied in the framework of density functional theory and transition state theory. It was found that the diffusion of hydrogen occurs through atom jump between octahedral positions surrounded by two iron atoms and four titanium atoms. In the case of hydrogen diffusion along the direction with a first-order transition state, the migration barrier was equal to 0.57 eV. A higher barrier of 0.99 eV was obtained along the direction with a second-order transition state. Analytical expressions were derived for the temperature-dependent diffusion coefficient of hydrogen in the alloy using Landman's method. It was shown that taking into account second-order transition states insignificantly affects the diffusion coefficient.